Happy accidents : the transformative power of "yes, and" at work and in life - Ahearn, David, 1969-; Ford, Frank, 1967-; Wilk, David, 1966- (John Wiley & Sons, Inc., 2017)
Stop saying 'no' to opportunity, and start saying 'yes' to possibility Happy Accidents is your personal guide to transforming your life. As we take on task after task, responsibility after responsibility, we lose sight of who we are and why we're doing what we do; we rush through the day completing a to-do list, but we never really seem to accomplish the things that are most important. What goals do you have for your life' What steps have you taken toward them today' Consider this book your guide to getting back on track to your dreams and help inspire those around you. It's not about doing more or doing less, it's about making what you do worthy of the effort. From forging new relationships, stepping out of your comfort zone, and reframing your work-start valuing these as empowering choices you get to make toward a particular goal every day. To preserve our precious time and energy, we often default to 'no, ' yet this only closes the door to our growth, while a 'yes' opens up a world of possibilities. The secret is adding 'yes, and' to our lives. This seductively simple turn of phrase opens the doors to better collaboration and positive relationships, and invites self-sustaining opportunities into our world. 'Yes, and' helps you get from where you are, as an individual or organization, to where want to be. No person or organization is an island, and none of us reaches our goals alone. This book shows you how to build on the power of open-mindedness, cultivate supportive relationships, and adopt a win-win mindset to reignite your purpose and unleash your best.-Harness the power of team collaboration, cooperation, and creativity -Reframe 'mistakes' and 'bad ideas' into 'Happy Accidents' that lead to opportunities -Communicate more effectively by learning how to listen actively and build on the pertinent information -Relinquish some degree of control to allow for more growth and discovery Children have a natural inclination toward curiosity. As we grow into adults, our curiosity gradually takes a back seat to obligations, responsibility, and duty-but that spark remains, and can be reignited. Don't spend your life adrift in a sea of 'could've, would've, should've'-take back your sense of purpose, positivity, joy, time, and energy with the power of Happy Accidents.